Teleconsultation in the prevention and control of older persons' health with regard to the COVID-19 pandemic: study protocol - Vanessa de Lima Silva; Carla Helena Augustin Schwanke; Adriana Falangola Benjamin Bezerra; Ana Paula de Oliveira Marques; Tatiana de Paula Santana da Silva; Carla Cabral dos Santos Accioly Lins; Maria Lúcia Gurgel da Costa; Anna Karla de Oliveira Tito Borba; Ilma Kruze Grande de Arruda; Maria das Graças Wanderley de Sales Coriolano (Brazilian Society of Geriatrics and Gerontology, 2022)
OBJECTIVE: To report the following study protocol: "Prevention program for older persons' health care focusing on the COVID-19 pandemic in the city of Recife - PE." METHODS: An action research study will be conducted with 151 older people of both sexes residing in the 8 health districts of Recife, Brazil. A teleconsultation service will be used to converse with participants. Activities will be organized into 2 moments: diagnosis and intervention. A guided conversation strategy will be used, dealing with issues related to coronavirus disease 2019 (COVID-19) prevention; social isolation; thoughts, emotions, and spirituality; family and community support; and personal development and ground rules for everyday life. The intervention with each older person will happen weekly for 12 weeks and will be characterized by listening to them and exchanging knowledge with the aim of bonding and optimizing adherence and compliance to COVID-19 prevention and control measures. Our data analysis will follow 3 approaches: cross-sectional (multivariate regression model), quasi-experimental (analysis of standardized residuals), and qualitative (interview and content analysis). EXPECTED RESULTS AND RELEVANCE: The construction of scientific knowledge is a key strategy when faced with the great challenge to global collective health presented by the COVID-19 pandemic. Data generated in this study may contribute to the improvement of knowledge, attitudes, and preventive practices, as well as to a good acceptance of the prevention program by older participants.